Effect of Comprehensive Lifestyle Modification and Meditation on Coronary Atherosclerosis and Its Risk Factors (Journal of Current and Advance Medical Research, 2020)
Background: Comprehensive lifestyle modification has an effect on coronary atherosclerosis.Objective: This study was performed to determine the effect of comprehensive lifestyle modification and meditation on coronary atherosclerosis.Methodology: This cohort study was done by Quantum Foundation, Dhaka, Bangladesh during the period of January 2010 to December 2014. Patients who had attended the 2-days long orientation program on comprehensive lifestyle modification, meditation and overview of coronary artery disease were included in the study. Participants who had attended ≥10 monthly and ≤2 monthly follow up & counseling session were defined as compliant and noncompliant group respectively. Patients were follow up for angiogram.Results: A total number of 32 patients were divided into compliant and noncompliant groups. Patient in the compliant group used to take heart healthy diet in 100.0% cases and avoided heart-unhealthy diet in 100.0% cases as well. Patients in the compliant group were also adherent to daily practice of meditation in 100.0% of cases and it was only 26.7% in case of non-compliant (P